Since \( JL \) is the perpendicular bisector of \( KM \), it means that \( KH \) is equal to \( HM \). Therefore, we can set the expressions for \( KH \) and \( HM \) equal to each other:
\[ 6y + 3 = 2y + 7 \]
Next, we can solve for \( y \):
- Subtract \( 2y \) from both sides:
\[ 6y - 2y + 3 = 7 \]
- Simplify:
\[ 4y + 3 = 7 \]
- Subtract \( 3 \) from both sides:
\[ 4y = 4 \]
- Divide by \( 4 \):
\[ y = 1 \]
Now that we have the value of \( y \), we can find the length of segment \( HM \):
Substituting \( y = 1 \) into the expression for \( HM \):
\[ HM = 2y + 7 = 2(1) + 7 = 2 + 7 = 9 \]
Thus, the length of segment \( HM \) is \( \boxed{9} \).